Novel Optical Chemical Sensor Based on Molecularly Imprinted Polymer Inside a Trench Micro-machined in Double Plastic Optical Fiber. (2016) - Cennamo, Nunzio; Testa, Genni; Marchetti, Simone; De Maria, Letizia; Bernini, Romeo; Zeni, Luigi; Pesavento, Maria
Abstract: For the detection of chemical agents in different environments, the combination of plastic optical fibers (POFs) and molecularly imprinted polymer (MIP) layers has been tested as a way to obtain a low cost, highly selective and sensitive surface plasmon resonance (SPR) chemical sensor. A novel type of optical chemical sensor based on POF-MIP has been designed and fabricated, and in this work it has been applied for the selective detection of dibenzyl disulfide (DBDS) in transformer oil. This analyte is important in the control of transformer oil, since it is responsible for the corrosive properties of the oil. The new optical sensor platform is based on two plastic optical fibers coupled through a polymer molecularly imprinted for DBDS. The new sensor has been found to be useful for the determination of DBDS in transformer oil.